ORIENTASI PENELITIAN PERTANIAN: MEMENUHI KEBUTUHAN PANGAN DALAM ERA GLOBALISASI - MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2001)
Since long ago Indonesia to face the food problem, even in the future will be a moreserious problem if agriculture sector as food producer not were work on seriously. Sincedecrease emphasize toward agriculture sector, in floods of import rice enter the domesticmarket so that to decrease farmer’s desire planting the rice, rely on sources of food on riceonly, and food diversification still limit of slogan or rhetoric entirely, has caused the nationalfood security system more and more become weak.It’s appeared trade-off between the goal of food security and the income growth offarmers, so in the framework of meet the national food can be met in a policy strategy of selfsufficiencyon trend. Its mean, to export when the national rice production surplus and toimport when national rice production deficit, cause the absolute self-sufficiency cannotdefended.To increase the household and national food security that faced on reduction thedepending on import food and depending on one kind source of food namely rice, so fooddiversification must be back encouraged that followed by research and development, actionprogram, and it’s to be as a national movement.Research of agriculture to meet the need of national food in globalization era, mainlyfood of non-rice carbohydrate in order to agribusiness orientation. Its mean, the research onevery subsystem of non-rice food agribusiness system, to aim increase the food production,producer income, and value added of food product mentioned, so that more and morecompetitive in domestic and national market.